Family involvement and business-owning group dynamics in the privately-held firm - Uhlaner, Lorraine Marie; Kincl, Tomáš, 1979-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2025)
This thesis provides an overview of the research conducted by habilitation candidate Lorraine Uhlaner regarding family involvement and business-owning group dynamics in the privately held firm. Her work has contributed substantially to the development of research on privately held firms, including both family businesses and nonfamily firms, including small and medium enterprises (SMEs). She has contributed to the conceptualization of concepts related to the owners, including owners ‘social capital, responsible ownership, and business-owning groups, as well as how to conceptualize and measure family involvement in the privately-held firm. One stream of her research compares family and nonfamily-owned and controlled firms, including antecedents and consequences of bridging behaviors and board behavior. In contrast, another research stream focuses on family firm heterogeneity. In this latter stream, differences in family governance practices, responsible ownership behaviors, professionalization, family noneconomic goals, and HRM practices are linked to family firm phenomena, including family firm performance. The middle sections of the thesis elaborate on the different concepts and how they have been applied in these two research streams. The last part of the thesis provides a brief overview of current works in progress and future research directions, including research aimed at a better understanding of how family firms innovate and why some family firms are more growth-oriented and entrepreneurial than others.
Vedoucí práce
Habilitační práce (doc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet